Blockchain Model for Secure Digital Identity Management and Healthcare Data Sharing - Olaoye N. S; Alese B. K (Journal of Intelligent Data Analysis and Computational Statistics (p-ISSN: 3049-3056 e-ISSN: 3048-7080), 2026)
As digital ecosystems evolve, the limitations of centralized identity management systems have become increasingly evident, particularly in healthcare environments where sensitive patient information is frequently exchanged across multiple institutions. Traditional identity models and federated single sign-on (SSO) systems create single points of failure and increase vulnerability to cyberattacks, identity theft, and unauthorized access. This study proposes a blockchain-based self-sovereign identity (SSI) framework for secure healthcare data sharing. The model integrates decentralized identifiers (DIDs), smart contracts, and zero-knowledge proofs (ZKPs) to enable secure identity verification and selective disclosure of sensitive information without exposing raw patient data. A layered architecture is adopted to separate trust management from data storage, combining user-centric identity portals, blockchain-based identity services, and off-chain storage using the InterPlanetary File System (IPFS). The framework ensures that healthcare records remain encrypted and under patient control while maintaining transparency and tamper resistance through blockchain audit mechanisms. A lightweight prototype was developed using Python and Streamlit to simulate healthcare access workflows and contextual risk evaluation. Experimental findings demonstrate that integrating decentralized identity, consent enforcement, and contextual access control enhances anomaly detection and improves healthcare data security. The proposed framework provides a scalable and privacy-preserving foundation for secure digital identity management in healthcare systems.